Infusing Technology in the 6-12 Classroom : A Guide to Meeting Today's Academic Standards - Morrison, Valerie; Vanderwerff, Tim; Novak, Stephanie (Book collections on Project MUSE., 2019)
"Perhaps your district provides current technology development for staff on a regular basis and has instructional coaches to help teachers infuse technology into their curriculum to meet various academic standards. But in reality, most districts don't have this kind of support. In this book (the second in a two-book series), you'll learn how to shift your instructional practice and leverage technology to meet today's curriculum education standards for grades 6-12. This book doesn't cover every 6-12 national standard, but identifies the standards with a technology component and provides resources and lessons to help you teach those standards effectively. This book serves as a coach, showing you how to integrate the tech requirements found within the standards into your everyday curriculum. With the implementation of these strategies, you'll help your students become self-directed and critical readers, writers and thinkers so they're better prepared for the future!"